Arrowhead-research on Design of Compound-UAV with Fenestron. (2015) - Wei, Shen; Lili, Hou
Abstract: New UAV products have recently expanded its support offerings to satisfy customers' increasingly improved requests, including higher sensitivity, better resolution, smaller volume, lighter weight, more flexible flight mode. Furthermore, miniaturization and high survivability are also main goals which current designers pursue. According to analysis on maturation of recent technique and comparison between different kinds of configuration, at the same time of maintaining the performance of low speed of classical aircraft, a solution is determined which turned out to be a multiplex-design with fenestron-system and coaxial-propeller.